Variability of treponemes in the rumen of ruminants - Sikorová, L; Piknová, M; Javorský, P; Guczyńska, W; Kasperowicz, A; Michałowski, T; Pristas, P (Folia microbiologica, 2010)
Complete 16S rRNA sequences were determined of recently proposed new species of treponemes designated strain S and T. Sequence comparison indicated that both species belong to the Treponema saccharophilum cluster, having thus at least 5 cultivable representatives. Phylogenetic analysis of available GenBank 16S rRNA sequences revealed two phylogenetically distant treponema clusters (T. saccharophilum cluster and T. bryantii cluster). Surprisingly, while among cultivated treponemes dominate T. saccharophilum cluster members, detailed analysis showed that all treponema-like sequences obtained by culture independent 16S rRNA methods belong to the T. bryantii cluster, from which only two cultivable representatives have so far been known. Meta-analysis of available data revealed that treponemes are an infrequent and minor group of bacteria, representing less than 2.4% of total rumen bacteria.
Keywords: bachor; DNA bakterií; DNA, Ribosomal; Phylogeny; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; RNA ribozomální 16S; Cluster Analysis; Rumen; zvířata; Colony Count, Microbial; RNA, Ribosomal, 16S; přežvýkavci; sekvenční analýza DNA; DNA, Bacterial; Treponema; fylogeneze; počet mikrobiálních kolonií; shluková analýza; ribozomální DNA; Animals; Ruminants